Children and animal abuse: Criminological, victimological and criminal justice aspects - Batrićević Ana (Temida, 2011)
Animal abuse represents a complex social, psychological, criminological, victimological and legal phenomenon whose gravity is increased if a child appears either as the perpetrator or as the observer of violence against animals. Etiology and phenomenology of animal abuse suggest that it tends to overlap with various deviant, delinquent and criminal activities, including physical, emotional and sexual abuse of family or other community members, alcohol and drug abuse, illegal gambling and betting and membership of children and adolescents in street gangs. The author discusses fundamental reasons, causes and motives for animal abuse committed by children as well as the devastating impact of children’s exposure to the scenes of animal abuse on their future delinquent behavior. She emphasizes the link between animal abuse and family violence and analyzes the position of a child as a direct or indirect victim in such situations. In addition, the author estimates the efficiency of existing mechanisms of prevention and state reaction to such behaviours and suggests solutions, which are accepted in comparative law, as potential role models.